Analysis of visualization index using technique of simultaneous laparoscopic operations - Halei, M.; Dzubanovskyi, I.; Marchuk, I. (Journal of Education, Health and Sport, 2020)
Fatigue is a temporary decrease in the efficiency of an organism or organ due to intensive or long-term work, which is manifested in a decrease in quantitative and qualitative indicators of work and deterioration of coordination of work functions. Groups of simultaneous operations (411 patients) and group of single operations (746 patients) were formed. In both groups these changes were insignificant in most cases (except for marginal values in obese patients III, there were 6 such cases in the first group and8 inthe second), corrections of the port administration scheme were performed when performing vertical gastrectomy in both groups. After the calculation, the average deviations were1.2 cmin the first group and1.4 cmin the second. When using a laparoscope with a viewing angle of 0 o, the approach distance of the laparoscope with its own method of access on average during normal surgery is (6.92 ± 0.306) cm and is slightly smaller than standard methods, the average value of the studied parameter in the control group is - (6.98 ± 0.258) cm (p <0.001). Visualisation during simultaneous laparoscopic operations using our developed technique was on the level with single laparoscopic operation, performed classically.